Web Based Leave Management System (Case Study of PT Java Pacific): Sistem Manajemen Cuti Berbasis Web (Studi Kasus PT Java Pasific) - Setiawan, Andri; Sumarno, Sumarno (Universitas Muhammadiyah Sidoarjo, 2023)
PT. Java Pacific has the obligation to provide leave entitlements for all employees, for the process of implementing, managing, calculating, reimbursement of leave being the task of the Human Resources Division of PT. Java Pacific. The objectives of this research include. Design and build a user-friendly web-based leave permit system. Method The method used in the development of this website-based leave application information system uses the RAD method, because it suits the needs of fast application development and has clear needs. The results obtained in this study are a leave management system that can facilitate monitoring data reporting in submitting leave at PT Java Pacific.